EMPOWERING RURAL NAGALAND: EXPLORING THE ROLE OF RADIO AS A CATALYST FOR DEVELOPMENT AND SOCIAL CHANGE - Longkumer, Wapangsungla; Das, Arjun (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The data analysis delves into the diverse patterns of information acquisition and awareness among respondents in Kohima and Mon districts. While Kohima exhibits higher rates of current affairs information acquisition, Mon district showcases greater unawareness of government schemes. Statistical analysis hints at a potential relationship between district and access to current affairs information and awareness of government schemes, albeit not achieving conventional significance levels. Moreover, differences in learning inclinations and media preferences emerge, with Mon district displaying more interest in learning new skills and a preference for radio as a medium for disseminating information. Notably, perceptions regarding radio’s impact and effectiveness vary significantly between districts, with Mon respondents reporting overwhelmingly positive impacts. These findings emphasize the need for tailored communication strategies and program development to address regional differences effectively, highlighting the potential of radio as a potent tool for information dissemination and social influence. Such insights can guide policymakers and communicators in crafting inclusive initiatives conducive to socio-economic development and empowerment in Kohima and Mon districts.